Alain Dewerpe et l’histoire dormante du secret - Pascal Engel (L'Atelier du CRH)
Alain Dewerpe's Espion (Gallimard 1995) is not only a pioneering work on a multifaceted activity which has many historical, sociological and political implications. It is also a deep anthropological and philosophical analysis of the essence of secret, which points, beyond the historical contexts, towards the permanent features of an historical epistemology of the spreading and hiding of knowledge.